Masculinities in a feminist pedagogy: lessons for transformative gender and agriculture training - Mwiine, Amon Ashaba; Mangheni, Margaret Najjingo; Asiimwe, Elizabeth; Businge, Martha; Shimali, Fred; Sanya, Losira Nasirumbi (Frontiers in Sociology, 2024)
Masculinities and femininities are closely interconnected with men and women farmers’ everyday lives; hence critical reflection on these interconnections should be central in gender training in agriculture. While a focus on men and masculinities is crucial for sustainable transformation of deep-rooted gender norms and practices that limit the attainment of gender equality, there are insufficient empirically tested pedagogical models for this purpose. We share a case study, the Gender Responsive Researchers Equipped for Agricultural Transformation (GREAT) model, which incorporates masculinities in a feminist pedagogy. We use external monitoring, evaluation, and learning data for two case study courses that integrate gender in plant breeding, seed systems, and agronomy to demonstrate the efficacy of integrating the concept of masculinity and reflections on male farmers’ expectations, behaviors, and practices within a feminist approach to gender training. We conclude that feminist pedagogical practices offer insights into how gender training can integrate a masculinities perspective to move beyond divisive and narrow gender polarities towards addressing masculine norms that often hinder the attainment of gender transformation.